Hubungan antara Kepercayaan Organisasi dengan Organizational Citizenship Behavior (OCB) Pegawai Pusat Pendidikan dan Pelatihan Bea Dan Cukai Jakarta Timur - Suherman, Hariyani Priscilia; Deswary, Dwi; Sari, Eliana (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2017)
This research set aims to discover the relation between organizational trust and organizational citizenship behavior at Pusat Pendidikan dan Pelatihan Bea dan Cukai East Jakarta. The research variable is organizational trust as independent variabel (X) and OCB as dependent variable (Y). The method used in this research is a survey method. To collect the data from respondent researcher use an instrument for both variable organizational trust and OCB. Data analyzing techniques to test the hypothesis using product moment. Before using the product moment researcher has to test the requirement test that cover normality test and liniearity test. From the result of hypothesis test for significance correlation researcher obtain Tscore > Ttable, Tscore = 31,78 and Ttable = 1,995. From the score we can conclude that the hypothesis being submitted is accepted and the nil hypothesis is rejected. From the result of the research can be concluded there is a positive relation between organizational trust and organizational citizenship behavior of employee at Pusat Pendidikan dan Pelatihan Bea dan Cukai East Jakarta. The result also sow the contribution of organizational trust for OCB is 93,61%. From the score can be described that the organizational trust giving a big amount of contribution for the enhancement of employee OCB. However to give the positive influence on OCB employee required another factor and not just organizational trust but also another factor that could increase the influence of OCB.